Waterproof component and electronic device having the same, waterproof method using insert molded body, and waterproof method for electronic device
By adding a specific amount of inorganic filler material to the thermoplastic resin, the heat resistance and waterproofness of the embedded waterproofing parts are improved, and the problem of difficult waterproofness in the prior art is solved, and the effect of maintaining efficient waterproofness after the reflow welding process is achieved.
Patent Information
- Application Number
- CN202080015863.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-02-25
- Filing Date
- 2020-02-21
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2040-02-21
AI Technical Summary
In the prior art, the waterproof member embedded in the molded body is difficult to maintain waterproofness after the reflow welding step, and the resin composition has low heat resistance and is prone to deform and melt in the heating step.
By adding a specific amount of spherical or plate-like inorganic filler material to the thermoplastic resin, the heat resistance and water resistance are improved, and it is ensured that sufficient water resistance can be maintained after the reflow welding process.
It is realized that even after the reflow welding process or other heating process, the waterproof components can still maintain sufficient waterproofness and are suitable for high-temperature environments.
Smart Images

Figure SMS_1 
Figure HDA0003221924060000011 
Figure HDA0003221924060000012
Abstract
Description
Technical Field
[0001] The present invention relates to a waterproof component, an electronic device having the waterproof component, a waterproof method using an insert molded body, a waterproof method for electronic devices, and the like. Background Art
[0002] In recent years, electronic devices such as smartphones are increasingly requiring waterproof properties. The external connection terminals of such electronic devices are typically a composite of a resin or resin composition and a metal component, and the metal component is often exposed to the outside, so waterproofing at the joint surface of the resin or resin composition and the metal becomes a problem. At the same time, as a method for manufacturing a printed circuit board to which electronic components are joined, the use of surface mounting is expanding, in which lead-free solder paste is printed on a printed circuit board, electronic components are mounted thereon, and then the surface is heated in a reflow oven at about 260°C where the lead-free solder melts. Although surface mounting can achieve miniaturization of printed circuit boards and improve productivity, the mounted components generate stress corresponding to the difference in expansion and contraction characteristics between the metal component and the resin or resin composition during the reflow process and the subsequent cooling process, and a small gap is easily generated between the metal component and the resin or resin composition, making it difficult to maintain waterproof properties.
[0003] Therefore, as a conventional waterproofing method for such external connection terminals, there is a method using a sealing material such as an elastomer (Patent Document 1, etc.) However, there are problems such as the inability to complete the components in one process due to the installation of the elastomer, difficulty in miniaturization, and the elastomer itself and its installation process incurring costs.
[0004] Therefore, a method for manufacturing a waterproof member by insert molding has been proposed, in which a resin or a resin composition is injection-molded and integrally joined to a metal member inserted into a mold (Patent Documents 2, 3, 4, etc.).
[0005] For example, Patent Document 2 discloses a polyamide resin composition containing specific branched molecules, fillers, impact resistance improvers, etc., and a resin-metal composite composed of the resin composition. Patent Document 3 discloses a resin composition containing a polyamide resin having a melting point of 140° C. to less than 210° C., a flaky filler, and a fibrous filler, and an insert molding resin composition composed of the resin composition.
[0006] In addition, Patent Document 4 discloses a resin composition composed of an aromatic polyamide resin, a liquid crystal polymer resin, a thermoplastic resin such as a styrene polymer mainly having a syndiotactic structure, an ethylene copolymer or polyamide 46, and an inorganic filler, and a semiconductor element storage package composed of the resin composition.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application Publication No. 2002-33155
[0010] Patent Document 2: Japanese Patent Application Publication No. 2014-141630
[0011] Patent Document 3: Japanese Patent Application Publication No. 2003-321606
[0012] Patent Document 4: Japanese Patent Application Publication No. 2002-105333 Summary of the invention
[0013] Problems to be solved by the invention
[0014] However, the resin used in the resin compositions of the above-mentioned patent documents 2 and 3 has low heat resistance, and if applied to surface mounting, it may be deformed or melted in the reflow process. In addition, in these patent documents 2 and 3, there is no teaching on the reflow process passability.
[0015] In addition, in Patent Document 4, regarding ethylene copolymers, the heat resistance and mechanical strength of molded products are sometimes reduced, and burrs are increased. In addition, regarding molded products containing polyamide 46, due to the increased water absorption, connection and quality are sometimes poor due to dimensional changes and blistering during the surface mounting process, and there is still a problem in balancing the passability of the surface mounting reflow process and waterproofness.
[0016] That is, an object of the present invention is to provide a waterproof component as an insert molded body having sufficient waterproof properties even after a heating process such as a reflow process, and an electronic device including the waterproof component.
[0017] Means for solving problems
[0018] The present inventors have conducted intensive studies and have found that, in a waterproof component which is an insert molded body comprising a thermoplastic resin composition and a metal component, by adding a specific amount of a specific spherical inorganic filler or a plate-like inorganic filler to the thermoplastic resin used, the waterproof property after the reflow process is improved. Based on this finding, the inventors have further repeated studies and completed the present invention.
[0019] The present invention relates to the following [1] to
[16] .
[0020] [1] A waterproof component which is an insert molded body comprising a thermoplastic resin composition and a metal component,
[0021] The thermoplastic resin composition comprises a thermoplastic resin (A) and an inorganic filler (B).
[0022] The content of the inorganic filler (B) is 8 to 130 parts by mass relative to 100 parts by mass of the thermoplastic resin (A).
[0023] The inorganic filler (B) is at least one of a spherical inorganic filler (B1) and a plate-like inorganic filler (B2),
[0024] The average particle size of the spherical inorganic filler (B1) is 2 μm or more and 200 μm or less.
[0025] The plate-like inorganic filler (B2) has an average particle size of 2 μm or more and 200 μm or less, and an average aspect ratio of 10 or more and 200 or less.
[0026] [2] The waterproof member according to [1], wherein the thermoplastic resin (A) has a melting point of 280° C. or higher.
[0027] [3] The waterproof component according to [1] or [2], wherein the thermoplastic resin (A) is at least one selected from the group consisting of polyamide, liquid crystal polymer, polyphenylene sulfide, and a styrene polymer mainly having a syndiotactic structure.
[0028] [4] The waterproof member according to any one of [1] to [3], wherein the thermoplastic resin (A) is a polyamide in which 50 to 100 mol % of the diamine units are aliphatic diamine units having 4 to 18 carbon atoms.
[0029] [5] The waterproof member according to any one of [1] to [4], wherein the inorganic filler (B) is at least one selected from glass beads, spherical silica, mica, glass flakes, and kaolin.
[0030] [6] The waterproof member according to [5], wherein the inorganic filler (B) is at least one selected from glass beads and spherical silica.
[0031] [7] The waterproof member according to any one of [1] to [6], which is used for an application suitable for a surface mounting process.
[0032] [8] The waterproof component according to any one of [1] to [7], which is an external connection terminal.
[0033] [9] The waterproof component according to any one of [1] to [8], which is a switch.
[0034]
[10] An electronic device comprising the waterproof component according to any one of [1] to [9].
[0035]
[11] The electronic device according to
[10] , which is a portable electronic device.
[0036]
[12] A waterproofing method using an insert molded body comprising a thermoplastic resin composition and a metal part, wherein the method uses the following thermoplastic resin composition:
[0037] The thermoplastic resin composition comprises a thermoplastic resin (A) and an inorganic filler (B).
[0038] The content of the inorganic filler (B) is 8 to 130 parts by mass relative to 100 parts by mass of the thermoplastic resin (A).
[0039] The inorganic filler (B) is at least one of a spherical inorganic filler (B1) and a plate-like inorganic filler (B2),
[0040] The average particle size of the spherical inorganic filler (B1) is 2 μm or more and 200 μm or less.
[0041] The plate-like inorganic filler (B2) has an average particle size of 2 μm or more and 200 μm or less, and an average aspect ratio of 10 or more and 200 or less.
[0042]
[13] Use of an insert molded body comprising a thermoplastic resin composition and a metal part for waterproofing, wherein the thermoplastic resin composition is used in the above use:
[0043] The thermoplastic resin composition comprises a thermoplastic resin (A) and an inorganic filler (B).
[0044] The content of the inorganic filler (B) is 8 to 130 parts by mass relative to 100 parts by mass of the thermoplastic resin (A).
[0045] The inorganic filler (B) is at least one of a spherical inorganic filler (B1) and a plate-like inorganic filler (B2),
[0046] The average particle size of the spherical inorganic filler (B1) is 2 μm or more and 200 μm or less.
[0047] The plate-like inorganic filler (B2) has an average particle size of 2 μm or more and 200 μm or less, and an average aspect ratio of 10 or more and 200 or less.
[0048]
[14] A method for waterproofing an electronic device, the method comprising using the waterproof member described in any one of [1] to [7] as an external connection terminal.
[0049]
[15] A method for waterproofing an electronic device, the method comprising using the waterproof component according to any one of [1] to [7] as a switch.
[0050]
[16] A method for producing a waterproof component, comprising insert molding a thermoplastic resin composition and a metal component.
[0051] The thermoplastic resin composition comprises a thermoplastic resin (A) and an inorganic filler (B).
[0052] The inorganic filler (B) is at least one of a spherical inorganic filler (B1) and a plate-like inorganic filler (B2),
[0053] The average particle size of the spherical inorganic filler (B1) is 2 μm or more and 200 μm or less.
[0054] The plate-like inorganic filler (B2) has an average particle size of 2 μm or more and 200 μm or less, and an average aspect ratio of 10 or more and 200 or less,
[0055] The thermoplastic resin composition is obtained by melt-kneading 8 to 130 parts by mass of the inorganic filler (B) with respect to 100 parts by mass of the thermoplastic resin (A).
[0056] Effects of the Invention
[0057] According to the present invention, it is possible to provide a waterproof component as an insert molded body having sufficient waterproof properties even after a heating step such as a reflow process, and an electronic device including the waterproof component. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] [ Figure 1 ] is a photograph of a sample used in the red ink test of the embodiment.
[0059] [ Figure 2 ] is used to illustrate the red ink test of the embodiment Figure 1 Schematic diagram of the XX' line cross-section.
[0060] [ Figure 3 ] is a photograph showing a sample for explaining the determination of the red ink test of the embodiment. DETAILED DESCRIPTION
[0061] Hereinafter, the present invention will be described in detail.
[0062] The waterproof component of the present invention is an insert molded body comprising a thermoplastic resin composition and a metal component.
[0063] The thermoplastic resin composition comprises a thermoplastic resin (A) and an inorganic filler (B).
[0064] The content of the inorganic filler (B) is 8 to 130 parts by mass relative to 100 parts by mass of the thermoplastic resin (A).
[0065] The inorganic filler (B) is at least one of a spherical inorganic filler (B1) and a plate-like inorganic filler (B2),
[0066] The spherical inorganic filler (B1) has an average particle size of 2 μm to 200 μm, the plate-like inorganic filler (B2) has an average particle size of 2 μm to 200 μm, and the average aspect ratio is 10 to 200.
[0067] By using the above-mentioned thermoplastic resin composition, the waterproof property (at the joining surface between the thermoplastic resin composition and the metal) of the insert molded body including the thermoplastic resin composition and the metal component is improved, and the waterproof property of the waterproof component becomes sufficient.
[0068] The reason is not clear, but it is considered that the use of the thermoplastic resin composition can alleviate the stress of the resin composition remaining after the insert molding process and the heating process, thereby preventing the generation of gaps at the bonding surface between the thermoplastic resin composition and the metal.
[0069] In addition, the inorganic filler material is shaped into a spherical shape or a plate shape, and the above conditions are satisfied for the average particle size and the aspect ratio, so that the inorganic filler material is unlikely to be anisotropic during the reflow process, and expands and contracts substantially uniformly, thereby preventing the formation of gaps at the interface between the thermoplastic resin composition and the metal. If the inorganic filler material is shaped like a rod, for example, it is thought that anisotropy is easily generated by heat treatment, and gaps are formed at the interface between the thermoplastic resin composition and the metal, and the desired waterproofness cannot be obtained.
[0070] (Thermoplastic resin (A))
[0071] The thermoplastic resin (A) used in the present invention is not particularly limited as long as it can impart the above-mentioned effects, and examples thereof include: polycarbonate; polyphenylene ether; polyphenylene sulfide (PPS); polysulfone; polyethersulfone; polyarylate; cyclic polyolefin; polyetherimide; polyamide; polyamideimide; polyimide; liquid crystal polymers such as aromatic polyesters and aromatic polyester amides; polyaminobismaleimide; polyetheretherketone; polystyrene, etc.
[0072] Among them, from the viewpoint of dimensional stability and heat resistance, at least one selected from polyamide, liquid crystal polymer, PPS and styrene polymers mainly having a syndiotactic structure is preferred, liquid crystal polymer and polyamide are more preferred, and polyamide is further preferred.
[0073] The melting point of the thermoplastic resin (A) is preferably 280° C. or higher, more preferably 285° C. or higher, and further preferably 295° C. or higher. When the melting point of the thermoplastic resin (A) is at least the above temperature, sufficient waterproofness can be maintained even when the waterproof component containing the thermoplastic resin (A) is used in an application exposed to a heating process such as a reflow process.
[0074] (Polyamide)
[0075] As the polyamide, a polyamide having a dicarboxylic acid unit and a diamine unit is preferred.
[0076] Examples of the dicarboxylic acid unit include aliphatic dicarboxylic acids such as oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedicarboxylic acid, dodecanedicarboxylic acid, dimethylmalonic acid, 2,2-diethylsuccinic acid, 2,2-dimethylglutaric acid, 2-methyladipic acid, and trimethyladipic acid; 1,3-cyclopentanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, The structural units include alicyclic dicarboxylic acids such as terephthalic acid, isophthalic acid, 1,4-naphthalene dicarboxylic acid, 2,6-naphthalene dicarboxylic acid, 2,7-naphthalene dicarboxylic acid, biphenyl dicarboxylic acid, 4,4'-biphenyl dicarboxylic acid, diphenylmethane-4,4'-dicarboxylic acid, and diphenyl sulfone-4,4'-dicarboxylic acid. These units may be one or more.
[0077] Furthermore, the polyamide may contain a structural unit derived from a trivalent or higher polycarboxylic acid such as trimellitic acid, trimesic acid, or pyromellitic acid within a range that does not impair the effects of the present invention and within a range that allows melt molding.
[0078] The polyamide preferably contains 50 to 100 mol% of diamine units as aliphatic diamine units having 4 to 18 carbon atoms, more preferably 60 to 100 mol% of diamine units as aliphatic diamine units having 4 to 18 carbon atoms, and more preferably 90 to 100 mol% of diamine units as aliphatic diamine units having 4 to 18 carbon atoms.
[0079] Examples of the aliphatic diamine unit having 4 to 18 carbon atoms include those derived from 1,4-butanediamine, 1,5-pentanediamine, 1,6-hexanediamine, 1,7-heptanediamine, 1,8-octanediamine, 1,9-nonanediamine, 1,10-decanediamine, 1,11-undecanediamine, 1,12-dodecanediamine, 1,13-tridecanediamine, 1,4-tetradecanediamine, 1,15-pentadecanediamine, 1,16-hexadecanediamine, 1,17-heptadecanediamine, 1,18-octadecanediamine, and 1,19-octadecanediamine. 1,1-dimethyl-1,4-butanediamine, 1-ethyl-1,4-butanediamine, 1,2-dimethyl-1,4-butanediamine, 1,3-dimethyl-1,4-butanediamine, 1,4-dimethyl-1,4-butanediamine, 2,3-dimethyl-1,4-butanediamine, 2-methyl-1,5-pentanediamine, 3-methyl-1,5-pentanediamine, 2,5-dimethyl-1,6-hexanediamine, 2,4-dimethyl-1,6-hexanediamine, 3,3-dimethyl 1,6-hexanediamine, 2,2-dimethyl-1,6-hexanediamine, 2,2,4-trimethyl-1,6-hexanediamine, 2,4,4-trimethyl-1,6-hexanediamine, 2,4-diethyl-1,6-hexanediamine, 2,2-dimethyl-1,7-heptanediamine, 2,3-dimethyl-1,7-heptanediamine, 2,4-dimethyl-1,7-heptanediamine, 2,5-dimethyl-1,7-heptanediamine, 2-methyl-1,8-octanediamine, 3-methyl-1,8-octanediamine, Structural units of branched aliphatic diamines such as 4-methyl-1,8-octanediamine, 1,3-dimethyl-1,8-octanediamine, 1,4-dimethyl-1,8-octanediamine, 2,4-dimethyl-1,8-octanediamine, 3,4-dimethyl-1,8-octanediamine, 4,5-dimethyl-1,8-octanediamine, 2,2-dimethyl-1,8-octanediamine, 3,3-dimethyl-1,8-octanediamine, 4,4-dimethyl-1,8-octanediamine, and 5-methyl-1,9-nonanediamine. These units may be one or more.
[0080] Among them, preferred are structural units derived from at least one selected from 1,4-butanediamine, 1,6-hexanediamine, 2-methyl-1,5-pentanediamine, 1,8-octanediamine, 2-methyl-1,8-octanediamine, 1,9-nonanediamine, 1,10-decanediamine, 1,11-undecanediamine, and 1,12-dodecanediamine, and more preferred are structural units derived from at least one selected from 1,4-butanediamine, 1,6-hexanediamine, 1,9-nonanediamine, 2-methyl-1,8-octanediamine, and 1,10-decanediamine.
[0081] When the diamine unit contains both a structural unit derived from 1,9-nonanediamine and a structural unit derived from 2-methyl-1,8-octanediamine, the molar ratio of the structural unit derived from 1,9-nonanediamine to the structural unit derived from 2-methyl-1,8-octanediamine is preferably in the range of structural unit derived from 1,9-nonanediamine / structural unit derived from 2-methyl-1,8-octanediamine = 95 / 5 to 40 / 60, and more preferably in the range of 90 / 10 to 50 / 50.
[0082] Moreover, depending on the application, the structural unit derived from 1,9-nonanediamine / the structural unit derived from 2-methyl-1,8-octanediamine=the range of 55 / 45 to 45 / 55 is sometimes preferable.
[0083] The diamine units in the above-mentioned polyamide may contain diamine units other than aliphatic diamine units having 4 to 18 carbon atoms within a range not impairing the effects of the present invention. Examples of such diamine units include structural units derived from aliphatic diamines such as ethylenediamine, 1,2-propylenediamine, and 1,3-propylenediamine; alicyclic diamines such as cyclohexanediamine, methylcyclohexanediamine, isophoronediamine, norbornanedimethylamine, and tricyclodecanedimethyldiamine; and aromatic diamines such as p-phenylenediamine, m-phenylenediamine, p-phenylenediamine, m-phenylenediamine, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylsulfone, and 4,4'-diaminodiphenylether. These units may be one or more.
[0084] The polyamide may also contain an aminocarboxylic acid unit. Examples of the aminocarboxylic acid unit include units derived from lactams such as caprolactam and lauryl lactam; aminocarboxylic acids such as 11-aminoundecanoic acid and 12-aminododecanoic acid. The content of the aminocarboxylic acid unit in the polyamide is preferably 40 mol% or less, and more preferably 20 mol% or less, relative to 100 mol% of the total of the dicarboxylic acid unit and the diamine unit of the polyamide.
[0085] The polyamide may contain a unit derived from a terminal blocking agent. The unit derived from the terminal blocking agent is preferably 1.0 to 10 mol %, more preferably 2.0 to 7.5 mol %, and even more preferably 2.5 to 6.5 mol % based on the diamine unit.
[0086] In order to set the units from the end-capping agent to the above-mentioned desired range, the end-capping agent can be added in a manner such that the end-capping agent is added to the above-mentioned desired range relative to the diamine when the polymerization raw materials are added. It should be noted that, considering that the monomer components volatilize during polymerization, it is desirable to slightly adjust the amount of the end-capping agent added when the polymerization raw materials are added so that the desired amount of units from the end-capping agent is introduced into the resulting resin.
[0087] As a method for obtaining the content of the unit derived from the end-capping agent in the above-mentioned polyamide, for example, there can be cited: as shown in Japanese Patent Publication No. 07-228690, the solution viscosity is measured, the total terminal group amount is calculated based on the relationship between the total terminal group amount and the number average molecular weight, and the amino group amount and the carboxyl group amount obtained by titration are subtracted from the total terminal group amount; using 1 H-NMR, and a method of determining based on the integrated value of the signals corresponding to the diamine unit and the unit derived from the terminal blocking agent, etc.
[0088] As the end-capping agent, a monofunctional compound having reactivity with a terminal amino group or a terminal carboxyl group can be used. Specifically, monocarboxylic acids, acid anhydrides, monoisocyanates, monoacyl halides, monoesters, monoalcohols, monoamines, etc. can be cited. From the viewpoints of reactivity and stability of the end-capping terminal, monocarboxylic acids are preferred as the end-capping agent for the terminal amino group, and monoamines are preferred as the end-capping agent for the terminal carboxyl group. In addition, from the viewpoints of ease of operation, monocarboxylic acids are more preferably used as the end-capping agent.
[0089] The monocarboxylic acid used as the end-capping agent is not particularly limited as long as it is reactive with an amino group, and examples thereof include: aliphatic monocarboxylic acids such as acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, caprylic acid, lauric acid, tridecanoic acid, myristic acid, palmitic acid, stearic acid, pivalic acid, and isobutyric acid; alicyclic monocarboxylic acids such as cyclopentanecarboxylic acid and cyclohexanecarboxylic acid; aromatic monocarboxylic acids such as benzoic acid, toluic acid, α-naphthoic acid, β-naphthoic acid, methylnaphthoic acid, and phenylacetic acid; and any mixture thereof. Among them, from the perspectives of reactivity, stability of the end-capping terminal, price, etc., at least one selected from acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, caprylic acid, lauric acid, tridecanoic acid, myristic acid, palmitic acid, stearic acid, and benzoic acid is preferred.
[0090] The monoamine used as the end-capping agent is not particularly limited as long as it is reactive with the carboxyl group, and examples thereof include: aliphatic monoamines such as methylamine, ethylamine, propylamine, butylamine, hexylamine, octylamine, decylamine, stearylamine, dimethylamine, diethylamine, dipropylamine, and dibutylamine; alicyclic monoamines such as cyclohexylamine and dicyclohexylamine; aromatic monoamines such as aniline, toluidine, diphenylamine, and naphthylamine; and any mixture thereof. Among them, at least one selected from butylamine, hexylamine, octylamine, decylamine, stearylamine, cyclohexylamine, and aniline is preferred in terms of reactivity, high boiling point, stability of the end-capping terminal, and price.
[0091] The polyamide can be produced by any method known as a method for producing polyamide, for example, by a solution polymerization method or an interfacial polymerization method using an acid chloride and a diamine as raw materials, a melt polymerization method using a dicarboxylic acid and a diamine as raw materials, a solid phase polymerization method, and a melt extrusion polymerization method.
[0092] The above-mentioned polyamide can be produced, for example, by first adding diamine, dicarboxylic acid and, if necessary, a catalyst and a capping agent at once to produce a nylon salt, and then heating and polymerizing at a temperature of 200 to 250° C. to form a prepolymer, and further performing solid phase polymerization, or polymerizing using a melt extruder. In the case of the final stage of polymerization by solid phase polymerization, it is preferably carried out under reduced pressure or under the flow of an inert gas. If the polymerization temperature is within the range of 200 to 280° C., the polymerization rate is large, the productivity is excellent, and coloring and gelation can be effectively suppressed. As the polymerization temperature in the final stage of polymerization by a melt extruder, it is preferably 370° C. or less. If the polymerization is carried out under such conditions, a polyamide with little decomposition and little deterioration can be obtained.
[0093] Examples of the catalyst that can be used when producing the polyamide include phosphoric acid, phosphorous acid, hypophosphorous acid, and salts or esters thereof. Examples of the salts or esters include salts of phosphoric acid, phosphorous acid, or hypophosphorous acid with metals such as potassium, sodium, magnesium, vanadium, calcium, zinc, cobalt, manganese, tin, tungsten, germanium, titanium, and antimony; ammonium salts of phosphoric acid, phosphorous acid, or hypophosphorous acid; and ethyl, isopropyl, butyl, hexyl, isodecyl, octadecyl, decyl, stearic acid, and phenyl esters of phosphoric acid, phosphorous acid, or hypophosphorous acid.
[0094] Furthermore, the polyamide may be any of crystalline polyamide, amorphous polyamide, and a mixture thereof.
[0095] Examples of the crystalline polyamide include polycaproamide (polyamide 6), polyhexamethylene adipamide (polyamide 66), polytetramethylene adipamide (polyamide 46), polyhexamethylene sebacamide (polyamide 610), polyhexamethylene dodecanamide (polyamide 612), polyundemethylene adipamide (polyamide 116), polybis(4-aminocyclohexyl)methane dodecanamide (polyamide PACM12), polybis(3-methyl-4-aminocyclohexyl)methane dodecanamide (polyamide dimethyl PACM12), polyundemethylene terephthalamide (polyamide 11T), and polyundemethylene hexahydroterephthalamide (polyamide 11 T(H)), polyundecanamide (polyamide 11), polydodecanamide (polyamide 12), polytrimethylhexamethylene terephthalamide (polyamide TMDT), polymethylene adipamide (polyamide MXD6), polyhexamethylene terephthalamide (polyamide 6T), polynonamethylene terephthalamide (polyamide 9T), polydecamethylene terephthalamide (polyamide 10T), polyhexamethylene isophthalamide (polyamide 6I), copolymers of polyamide 6I and polyamide 6T (polyamide 6I / 6T), copolymers of polyamide 6T and polyundecanamide (polyamide 11) (polyamide 6T / 11), and copolymers and mixtures thereof. It should be noted that the above-mentioned crystalline polyamide also includes substances in which the benzene rings of terephthalic acid and / or isophthalic acid are substituted by alkyl groups or halogen atoms.
[0096] Among the above-mentioned crystalline polyamides, polyamide 6, polyamide 66, polyamide 11, polyamide 12, polyamide 46, polyamide 6T, polyamide 9T, and polyamide 10T are preferred, polyamide 6, polyamide 66, polyamide 46, polyamide 6T, polyamide 9T, and polyamide 10T are more preferred, and polyamide 46, polyamide 6T, polyamide 9T, and polyamide 10T are further preferred. The above-mentioned crystalline polyamides may be used alone or in combination of two or more.
[0097] Examples of the amorphous polyamide include condensates of terephthalic acid / isophthalic acid / hexamethylenediamine, condensates of terephthalic acid / isophthalic acid / hexamethylenediamine / bis(3-methyl-4-aminocyclohexyl)methane, condensates of terephthalic acid / 2,2,4-trimethyl-1,6-hexamethylenediamine / 2,4,4-trimethyl-1,6-hexamethylenediamine, and condensates of isophthalic acid / 1,6-hexamethylenediamine / bis(3-methyl-4-aminocyclohexyl)methane. Condensation products of diphthalic acid / bis(3-methyl-4-aminocyclohexyl)methane / ω-laurolactam, polycondensation products of isophthalic acid / 2,2,4-trimethyl-1,6-hexanediamine / 2,4,4-trimethyl-1,6-hexanediamine, polycondensation products of terephthalic acid / isophthalic acid / 2,2,4-trimethyl-1,6-hexanediamine / 2,4,4-trimethyl-1,6-hexanediamine, etc. It should be noted that the above-mentioned amorphous polyamide also includes substances in which the benzene rings of terephthalic acid and / or isophthalic acid are substituted by alkyl groups or halogen atoms.
[0098] Among the above-mentioned amorphous polyamides, polycondensates of terephthalic acid / isophthalic acid / 1,6-hexanediamine, polycondensates of terephthalic acid / isophthalic acid / 1,6-hexanediamine / bis(3-methyl-4-aminocyclohexyl)methane, and polycondensates of terephthalic acid / 2,2,4-trimethyl-1,6-hexanediamine / 2,4,4-trimethyl-1,6-hexanediamine are preferred, and polycondensates of terephthalic acid / isophthalic acid / 1,6-hexanediamine and polycondensates of terephthalic acid / isophthalic acid / 1,6-hexanediamine / bis(3-methyl-4-aminocyclohexyl)methane are more preferred. The above-mentioned amorphous polyamides may be used alone or in combination of a plurality of them.
[0099] (Inorganic filler (B))
[0100] The inorganic filler (B) is at least one of a spherical inorganic filler (B1) and a plate-like inorganic filler (B2).
[0101] Examples of the spherical inorganic filler (B1) used in the present invention include spherical glass beads, spherical silica, hollow glass spheres, shira balls, titanium oxide, carbon black, mica, etc. These may be used alone or in combination of two or more.
[0102] Examples of the plate-like inorganic filler (B2) include plate-like mica, glass flakes, kaolin, talc, and layered silicates, etc. These may be used alone or in combination of two or more.
[0103] Among the inorganic fillers (B), at least one selected from spherical or plate-shaped glass beads, spherical silica, mica, glass flakes, and kaolin is preferred, at least one selected from glass beads, spherical silica, glass flakes, and mica is more preferred, and at least one selected from glass beads and mica is even more preferred.
[0104] The average particle size of the spherical inorganic filler (B1) used in the present invention is 2 μm or more and 200 μm or less, preferably 2 μm or more and 80 μm or less, more preferably 5 μm or more and 50 μm or less. In addition, from the viewpoint of formability, surface properties, and mechanical properties, the average particle size is preferably 200 μm or less, more preferably 80 μm or less, and further preferably 50 μm or less.
[0105] In the case of a plate-like inorganic filler (B2), the average particle size is 2 μm or more and 200 μm or less, preferably 2 μm or more and 80 μm or less, more preferably 5 μm or more and 50 μm or less. In addition, from the viewpoint of formability, surface properties, and mechanical properties, the average particle size is preferably 200 μm or less, more preferably 80 μm or less, and further preferably 50 μm or less. In addition, the average aspect ratio of the plate-like inorganic filler (B2) is 10 or more and 200 or less, preferably 10 or more and 100 or less, and more preferably 10 or more and 50 or less. In addition, from the viewpoint of formability, surface properties, and mechanical properties, the aspect ratio is 10 or more and 200 or less, preferably 10 or more and 100 or less, and more preferably 10 or more and 50 or less.
[0106] It should be noted that the "average particle size" of the spherical inorganic filler (B1) in this specification refers to the volume average particle size, and can be calculated by filling the pores with an aperture of 20 to 400 μm with an electrolyte solution and calculating the volume according to the change in the conductivity of the electrolyte solution when the particles pass through the electrolyte solution. Specifically, the volume average particle size of the spherical inorganic filler (B1) is the volume average particle size (arithmetic mean diameter in the volume-based particle size distribution) measured by using the Coulter method precision particle size distribution measuring device "Multisizer III" (BeckmanCoulter Co., Ltd.). It should be noted that when measuring, in accordance with "Reference MANUALFOR THE COULTER MULTISIZER" (1987) issued by Coulter Electronics Limited, the aperture (aperture) suitable for the particle size of the measured particles is used to calibrate the "Multisizer III" and measure.
[0107] Specifically, 0.1 g of spherical inorganic filler (B1) was dispersed in 10 mL of 0.1 wt % nonionic surfactant solution using a touch mixer and ultrasonic waves to prepare a dispersion. The dispersion was added dropwise with a dropper while slowly stirring in a beaker filled with an electrolyte for measurement "ISOTON (registered trademark) II" (manufactured by Beckman Coulter Co., Ltd.) installed on the "Multisizer III" main body, and the reading of the concentration meter on the "Multisizer III" main body screen was adjusted to about 10%. Then, according to the "Reference MANUAL FORTHE COULTER MULTISIZER" (1987) issued by Coulter Electronics Limited, the aperture size (diameter), Current (aperture current), Gain (gain), and Polarity (polarity of the inner electrode) were input into the "Multisizer III" main body, and the volume-based particle size distribution was measured by manual (manual mode). During the measurement, the beaker is stirred slowly to such an extent that bubbles do not enter, and the measurement is terminated at a time point after the particle size distribution of 100,000 spherical inorganic fillers (B1) is measured. The volume average particle size of the spherical inorganic filler (B1) is the average value of the particle sizes of the 100,000 spherical inorganic fillers (B1) measured, and means the arithmetic mean diameter in the volume-based particle size distribution.
[0108] In addition, the "average particle size" of the plate-like inorganic filler (B2) in this specification refers to the particle size of 50% of the cumulative mass, and can be measured by dispersing the plate-like inorganic filler (B2) in pure water and using a particle size distribution measuring device (such as "Microtrack MT3000" manufactured by Microtrack Bell) using a laser diffraction / scattering method.
[0109] In addition, the "average aspect ratio" of the plate-like inorganic filler (B2) in this specification is the value obtained by dividing the average particle size by the "average thickness", and the average thickness can be measured by the water surface particle film method described below. The plate-like inorganic filler (B2) is immersed in a 2% stearylamine toluene solution, and the upper liquid is removed and filtered, washed with acetone and air-dried. The water surface of a water tank filled with a certain amount of water is divided into three parts by two partitions that do not reach the bottom of the water tank. When the water is circulated by a water flow pump, the plate-like inorganic filler (B2) obtained by filtration is spread on the central water surface surrounded by two partitions. The dispersed mica is freely moved on the water surface by the water flow to make it evenly dispersed. Antistatic spray is used to assist dispersion as needed. At the time point when the plate-like inorganic filler (B2) is evenly dispersed, the pump switch is turned off to move one of the partitions to another, thereby forming a uniform film of the plate-like inorganic filler (B2). The end point of the movement was set just before wrinkles appeared in the membrane.
[0110] The average thickness is calculated according to the following formula, where A is the film area, t is the average thickness, W is the weight of the plate-like inorganic filler (B2), ρ is the density of the plate-like inorganic filler (B2), and 1-ε is the particle filling rate (=0.9).
[0111] t=W / (1-ε)ρA
[0112] The content of the inorganic filler (B) in the thermoplastic resin composition is 8 to 130 parts by mass, preferably 20 to 130 parts by mass, more preferably 30 to 130 parts by mass, further preferably 40 to 130 parts by mass, and further preferably 45 to 110 parts by mass, based on 100 parts by mass of the thermoplastic resin (A).
[0113] If the content of the inorganic filler (B) is less than 8 parts by mass, a sufficient waterproofing effect due to the inclusion of the inorganic filler (B) cannot be obtained. If the content of the inorganic filler (B) exceeds 130 parts by mass, melt kneading properties become poor.
[0114] When the thermoplastic resin composition contains both the spherical inorganic filler (B1) and the plate-like inorganic filler (B2), the content of the inorganic filler (B) refers to the total content of the spherical inorganic filler (B1) and the plate-like inorganic filler (B2).
[0115] (Other ingredients)
[0116] The thermoplastic resin composition used in the present invention may further contain other components other than the thermoplastic resin (A) and the inorganic filler (B), such as a mold release agent, an antioxidant, a heat stabilizer, a light stabilizer, a styrene-maleic anhydride copolymer (SMA), a lubricant, a nucleating agent, a crystallization delaying material, a hydrolysis inhibitor, an antistatic agent, a free radical inhibitor, a matting agent, an ultraviolet absorber, a flame retardant, an anti-dripping agent, a slip imparting agent, and an inorganic substance other than the above-mentioned inorganic filler (B) within a range not impairing the effects of the present invention.
[0117] Examples of the inorganic substance include carbon nanotubes, fullerenes, talc, wollastonite, zeolite, sericite, kaolin, clay, pyrophyllite, silica, bentonite, aluminum silicate, silicon oxide, magnesium oxide, aluminum oxide, zirconium oxide, iron oxide, calcium carbonate, magnesium carbonate, dolomite, calcium sulfate, barium sulfate, calcium hydroxide, magnesium hydroxide, aluminum hydroxide, glass fiber, milled fiber, glass powder, ceramic beads, boron nitride, silicon carbide, graphite, halloysite, vermiculite and other clay minerals.
[0118] The content of other components in the thermoplastic resin composition can be, for example, 50% by mass or less, preferably 20% by mass or less, more preferably 10% by mass or less, and further preferably 5% by mass or less.
[0119] In addition, since the heat resistance and mechanical strength of the molded product may be reduced and burrs may increase, it is preferable not to contain an ethylene-based copolymer including an elastomer or an ionomer.
[0120] The total content of the thermoplastic resin (A) and the inorganic filler (B) in the thermoplastic resin composition is, for example, preferably 50% by mass or more, more preferably 80% by mass or more, further preferably 90% by mass or more, and even more preferably 95% by mass or more.
[0121] (Metal Parts)
[0122] The metal constituting the metal parts used in the present invention is not particularly limited as long as it can be insert molded, and examples thereof include aluminum, copper, iron, tin, nickel, zinc, aluminum alloys, stainless steel and other alloys, etc. The surfaces thereof may also be plated with aluminum, tin, nickel, gold, silver and the like.
[0123] (Waterproof parts)
[0124] The waterproof member can be produced by insert molding a thermoplastic resin composition and a metal member.
[0125] The thermoplastic resin composition comprises a thermoplastic resin (A) and an inorganic filler (B).
[0126] The inorganic filler (B) is at least one of a spherical inorganic filler (B1) and a plate-like inorganic filler (B2),
[0127] The average particle size of the spherical inorganic filler (B1) is 2 μm or more and 200 μm or less.
[0128] The plate-like inorganic filler (B2) has an average particle size of 2 μm or more and 200 μm or less, and an average aspect ratio of 10 or more and 200 or less,
[0129] The thermoplastic resin composition is obtained by melt-kneading 8 to 130 parts by mass of the inorganic filler (B) relative to 100 parts by mass of the thermoplastic resin (A).
[0130] In the case of insert molding, any method known as insert molding, for example, injection insert molding, compression insert molding, etc., can be used.
[0131] It should be noted that, if necessary, after insert molding, further processing using ultrasonic welding, laser welding, vibration welding, thermal welding, hot melting, etc. may be performed.
[0132] In the component installation of electronic components mounted on a printed circuit board, an insertion installation process of soldering by dipping in a molten solder tank (dipping tank) has been applied in the past. On the other hand, in the surface installation that has been widely used in recent years, the solder paste is printed on the printed circuit board, and after the electronic components are installed thereon, it is usually heated at about 260°C in a reflow oven to melt the solder and join the printed circuit board and the electronic components. Although surface installation can achieve miniaturization of the printed circuit board and improve productivity, the installed components generate stress corresponding to the difference in expansion and contraction characteristics between the metal parts and the resin or resin composition in the reflow process and the subsequent cooling process, and a small gap is easily generated between the metal parts and the resin or resin composition, making it difficult to maintain waterproofness. The waterproof component of the present invention is not easy to deform even after a heating process such as a reflow process, so it is preferably used in the application of a surface mounting process using such a reflow process. It should be noted that, as needed, a heating process such as a reflow process can be applied multiple times.
[0133] The waterproof component of the present invention has excellent waterproof properties and is therefore useful as external connection terminals such as FPC connectors, BtoB connectors, card connectors, SMT connectors (coaxial connectors, etc.), memory card connectors; SMT relays; SMT bobbins; slots such as memory slots and CPU slots; switches such as command switches and SMT switches; sensors such as rotation sensors and acceleration sensors, etc., among which it is useful as a switch or external connection terminal of an electronic device and is particularly useful as a switch.
[0134] When the waterproof component of the present invention is used as a switch, when the outer dimensions of the insert molded body including the thermoplastic resin composition and the metal component are set to width×depth×thickness, the width is preferably 15 mm or less, more preferably 10 mm or less, and further preferably 5 mm or less, the depth is preferably 50 mm or less, more preferably 25 mm or less, and further preferably 5 mm or less, and the thickness is preferably 50 mm or less, more preferably 15 mm or less, and further preferably 3 mm or less. It should be noted that the depth of the outer dimensions is set to be longer than the width.
[0135] By using the waterproof member of the present invention particularly as a switch or an external connection terminal, electronic equipment can be effectively waterproofed.
[0136] Examples of electronic devices including the waterproof member of the present invention include portable electronic devices such as digital cameras and smartphones, but the present invention is not limited thereto.
[0137] That is, the present invention can also provide a waterproofing method using an insert molded article comprising the thermoplastic resin composition and a metal component, and use of the insert molded article for waterproofing.
[0138] Example
[0139] Hereinafter, the present invention will be described in more detail by way of examples, but the present invention is not limited to these examples at all.
[0140] In addition, the melting point and glass transition temperature of the thermoplastic resin (A) used in Examples and Comparative Examples were measured by the method shown below.
[0141] (Melting Point and Glass Transition Temperature of Thermoplastic Resin (A))
[0142] The melting point of the polyamide (PA9T described below) used as the thermoplastic resin (A) was determined by using a differential scanning calorimeter (DSC7020) manufactured by Hitachi High Tech Science Co., Ltd., and setting the peak temperature of the melting peak that appears when the temperature is raised from 30°C to 360°C at a rate of 10°C / min in a nitrogen atmosphere as the melting point (°C). It should be noted that when there are multiple melting peaks, the peak temperature of the melting peak on the highest temperature side is set as the melting point.
[0143] Thereafter, the sample was kept at a temperature 30°C higher than the melting point for 10 minutes to completely melt, then cooled to 40°C at a rate of 10°C / min and kept at 40°C for 10 minutes. When the temperature was again raised to a temperature 30°C higher than the melting point at a rate of 10°C / min, the midpoint of the step-like change of the DSC curve was set as the glass transition temperature.
[0144] [Examples 1 to 6 and Comparative Examples 1 to 3]
[0145] The thermoplastic resin (A) and other components shown in Table 1 are supplied to a twin-screw extruder (screw diameter 32 mm, L / D = 30, rotation speed 150 rpm, discharge volume 10 kg / h) manufactured by the Institute of Plastics Engineering through a hopper at the most upstream part, and the inorganic filler (B) shown in Table 1 is further supplied through a side feeder for melt kneading. The melt-kneaded thermoplastic resin composition is extruded into a bundle, cooled and cut to obtain pellets of the thermoplastic resin composition. It should be noted that the amounts of the thermoplastic resin (A), inorganic filler (B) and other components in Table 1 all refer to "parts by mass".
[0146] Using these pellets, evaluation as molded products (insert molded bodies) was performed by the following method.
[0147] [Red ink test (waterproof test)]
[0148] The thermoplastic resin composition obtained in each Example or Comparative Example was injection molded into a box mold (external dimensions: width 2.8 mm, depth 3.0 mm, thickness 1.3 mm) on a silver-plated copper substrate of an LED lead frame using an injection molding machine TR40EH manufactured by Sodick Co., Ltd. at a maximum temperature of 320° C., a mold temperature of 140° C., and an injection speed of 100 to 200 mm / s.
[0149] The following red ink test was performed using a sample obtained by heating the flat plate-shaped molded product obtained above twice under the following reflow conditions in a reflow device with a maximum temperature of 260° C.
[0150] Here, Figure 1 This is a photo of the sample above. Figure 2 Yes means Figure 1 Schematic diagram of the X-X' line cross-section of the sample photograph. Figure 2 As shown, the sample is an embedded molded body formed by an LED lead frame 1 and a box mold 2, and has a depression 3 for ink dripping for red ink testing, and the box mold 2 is formed by a thermoplastic resin composition 2. The depression has a discontinuous portion 4 in which a part of the LED lead frame is exposed and a part of the LED lead frame is missing. In addition, the box mold 2 has a gap 5 on the back side (the side without the depression 3), but the discontinuous portion 4 does not overlap with the gap 5. It should be noted that Figure 1 In the photograph of FIG. 1 , a ring-shaped portion is shown in the box mold 2. This is because the curved portion of the thermoplastic resin composition reflects light and thus looks like a ring.
[0151] (Reflow conditions):
[0152] The sample was heated from 25°C to 150°C over 60 seconds, then to 180°C over 90 seconds, and further to 260°C over 60 seconds. After being kept at 260°C for 20 seconds, the sample was cooled from 260°C to 100°C over 30 seconds, and after reaching 100°C, air was sealed and naturally cooled to 23°C.
[0153] (Red ink test)
[0154] Red ink (Stamp ink red manufactured by Lion Instruments Co., Ltd.) was dripped into the concave portion 3 of the box mold 2 formed of the thermoplastic resin composition, and the ink was removed after 5 minutes. Then, the box mold (thermoplastic resin composition) was removed from the LED lead frame, and it was confirmed whether the ink adhered to the back side of the LED lead frame opposite to the ink dripping side.
[0155] The case where ink did not adhere to the back side of the LED lead frame was judged as “no leakage.” On the other hand, the case where ink adhered to the back side of the LED lead frame was judged as “leakage.”
[0156] It should be noted that Figure 3 (3-1) in the figure is a photograph of the sample surface, the left side is before the red ink is added, and the right side is after the red ink is added. Figure 3 (3-2) is a photograph of the back of the sample before the red ink was added. Figure 3 (3-3) is a photograph showing the result of Example 1 judged as "no leakage" in the red ink test. Figure 3 (3-4) is a photograph showing the result of Comparative Example 1 judged as "leakage".
[0157] [Table 1]
[0158]
[0159] In addition, each component shown in Table 1 is as follows.
[0160] [Thermoplastic resin (A)]
[0161] PA9T: "Genesta GC31110", manufactured by Kuraray Co., Ltd., PA9T (polyamide in which the dicarboxylic acid unit is a terephthalic acid unit and the diamine unit is a 1,9-nonanediamine unit and a 2-methyl-1,8-octanediamine unit (molar ratio 85 / 15)), melting point 305°C, glass transition temperature 125°C
[0162] [Spherical inorganic filler (B1)]
[0163] Glass beads: "EGB731-PN", manufactured by Potters Barotini Co., Ltd., average particle size 20 μm
[0164] [Plate-shaped inorganic filler (B1)]
[0165] Mica: "S-325", manufactured by Repco Co., Ltd., average particle size 27 μm, average aspect ratio 30
[0166] [Other ingredients]
[0167] Glass fiber: "CS3J256S", manufactured by Nitto Bosho Co., Ltd., average fiber diameter 11μm, average fiber length 3mm
[0168] Flame retardant: "Exolit OP1230", manufactured by Clariant Chemicals
[0169] · Antioxidant-1: "Irganox 1098", manufactured by BASF Japan
[0170] · Antioxidant-2: "Irgafos 168", manufactured by BASF Japan
[0171] Nucleating agent: Carbon black "#980B", manufactured by Mitsubishi Chemical Corporation
[0172] Release agent: High-density polyethylene "HI WAX 200P", manufactured by Mitsui Chemicals, Ltd.
[0173] In Example 1, Figure 3 As shown in (3-3), no red ink adheres to the back of the LED lead frame after the resin composition is removed. It can be seen that in Example 1, even after the reflow process, no gap is generated between the LED lead frame and the thermoplastic resin composition, and an embedded molded body with excellent waterproofness can be obtained. In addition, it can be seen that the same results as in Example 1 are obtained in Examples 2 to 6, and an embedded molded body with excellent waterproofness can be obtained.
[0174] On the other hand, in Comparative Example 1, Figure 3 As shown in (3-4), red ink adheres to the back of the LED lead frame after the resin composition is removed. That is, it is believed that since Comparative Example 1 uses rod-shaped glass fibers instead of the inorganic filler (B), a gap is generated between the LED lead frame and the thermoplastic resin composition through the reflow process, and the red ink penetrates from the discontinuous portion 4, resulting in poor waterproofness. In addition, in Comparative Examples 2 and 3, similarly to Comparative Example 1, red ink also adheres to the back of the LED lead frame, resulting in poor waterproofness.
[0175] Therefore, it can be seen from the comparison between the examples and the comparative examples that the waterproof member of the present invention is excellent in waterproofness after the reflow process.
[0176] Industrial Applicability
[0177] According to the present invention, a waterproof component as an insert molded body having sufficient waterproof properties even after a heating process such as a reflow process can be provided. The waterproof component is particularly useful as an external connection terminal of an electronic device.
[0178] Explanation of symbols
[0179] 1.LED lead frame (metal parts)
[0180] 2. Box mold formed from thermoplastic resin composition
[0181] 3. Depression for ink dripping
[0182] 4. Discontinuous parts of LED lead frame
[0183] 5. Clearance
Claims
1. A waterproof component, which is an insert molded body comprising a thermoplastic resin composition and a metal component, The thermoplastic resin composition comprises a thermoplastic resin (A) and an inorganic filler (B), wherein the thermoplastic resin (A) is polyamide. The content of the inorganic filler (B) is 8 to 130 parts by mass relative to 100 parts by mass of the thermoplastic resin (A). The inorganic filler (B) is at least one of a spherical inorganic filler (B1) and a plate-like inorganic filler (B2), The average particle size of the spherical inorganic filler (B1) is 2 μm or more and 200 μm or less. The plate-like inorganic filler (B2) has an average particle size of 2 μm or more and 200 μm or less, and an average aspect ratio of 10 or more and 200 or less, The inorganic filler (B1) is selected from at least one of spherical glass beads, spherical silica, hollow glass balls, white sand balls, titanium oxide, carbon black, and spherical mica. The inorganic filler (B2) is selected from at least one of plate-like mica, glass flakes, kaolin, talc, and layered silicates.
2. The waterproof component according to claim 1, wherein: The melting point of the thermoplastic resin (A) is 280° C. or higher.
3. The waterproof component according to claim 1, wherein: The thermoplastic resin (A) is a polyamide in which 50 mol % to 100 mol % of diamine units are aliphatic diamine units having 4 to 18 carbon atoms.
4. The waterproof component according to claim 1, wherein: The inorganic filler (B) is at least one selected from the group consisting of spherical glass beads, spherical silica, spherical mica, plate-like mica, glass flakes, and kaolin.
5. The waterproof component according to claim 4, wherein: The inorganic filler (B) is at least one selected from the group consisting of spherical glass beads, spherical mica, and plate-like mica. The waterproof member according to claim 1, which is used for applications suitable for surface mounting processes. The waterproof member according to claim 1 , which is an external connection terminal. The waterproof component according to claim 1 , which is a switch. 9 . An electronic device comprising the waterproof member according to claim 1 .
10. The electronic device according to claim 9, which is a portable electronic device.
11. A waterproofing method using an insert molded body comprising a thermoplastic resin composition and a metal component, wherein the method uses the following thermoplastic resin composition: The thermoplastic resin composition comprises a thermoplastic resin (A) and an inorganic filler (B), wherein the thermoplastic resin (A) is polyamide. The content of the inorganic filler (B) is 8 to 130 parts by mass relative to 100 parts by mass of the thermoplastic resin (A). The inorganic filler (B) is at least one of a spherical inorganic filler (B1) and a plate-like inorganic filler (B2), The average particle size of the spherical inorganic filler (B1) is 2 μm or more and 200 μm or less. The plate-like inorganic filler (B2) has an average particle size of 2 μm or more and 200 μm or less, and an average aspect ratio of 10 or more and 200 or less, The inorganic filler (B1) is selected from at least one of spherical glass beads, spherical silica, hollow glass balls, white sand balls, titanium oxide, carbon black, and spherical mica. The inorganic filler (B2) is selected from at least one of plate-like mica, glass flakes, kaolin, talc, and layered silicates.
12. Use of an insert molded body comprising a thermoplastic resin composition and a metal part for waterproofing, wherein the thermoplastic resin composition is used: The thermoplastic resin composition comprises a thermoplastic resin (A) and an inorganic filler (B), wherein the thermoplastic resin (A) is polyamide. The content of the inorganic filler (B) is 8 to 130 parts by mass relative to 100 parts by mass of the thermoplastic resin (A). The inorganic filler (B) is at least one of a spherical inorganic filler (B1) and a plate-like inorganic filler (B2), The average particle size of the spherical inorganic filler (B1) is 2 μm or more and 200 μm or less. The plate-like inorganic filler (B2) has an average particle size of 2 μm or more and 200 μm or less, and an average aspect ratio of 10 or more and 200 or less, The inorganic filler (B1) is selected from at least one of spherical glass beads, spherical silica, hollow glass balls, white sand balls, titanium oxide, carbon black, and spherical mica. The inorganic filler (B2) is selected from at least one of plate-like mica, glass flakes, kaolin, talc, and layered silicates. 13 . A method for waterproofing an electronic device, comprising using the waterproof member according to claim 1 as an external connection terminal.
14. A method for waterproofing an electronic device, comprising using the waterproof member according to any one of claims 1 to 6 as a switch.
15. A method for manufacturing a waterproof component, wherein: Insert molding of a thermoplastic resin composition and a metal part, The thermoplastic resin composition comprises a thermoplastic resin (A) and an inorganic filler (B), wherein the thermoplastic resin (A) is polyamide. The inorganic filler (B) is at least one of a spherical inorganic filler (B1) and a plate-like inorganic filler (B2), The average particle size of the spherical inorganic filler (B1) is 2 μm or more and 200 μm or less. The plate-like inorganic filler (B2) has an average particle size of 2 μm or more and 200 μm or less, and an average aspect ratio of 10 or more and 200 or less, The inorganic filler (B1) is selected from at least one of spherical glass beads, spherical silica, hollow glass balls, white sand balls, titanium oxide, carbon black, and spherical mica. The inorganic filler (B2) is selected from at least one of plate-like mica, glass flakes, kaolin, talc, and layered silicate. The thermoplastic resin composition is obtained by melt-kneading 8 to 130 parts by mass of the inorganic filler (B) based on 100 parts by mass of the thermoplastic resin (A).
Citation Information
Patent Citations
Polyamide
JP1995228690A
Waterproof connector
JP2002033155A
Thermoplastic resin composition, method for producing the same, and package for receiving semiconductor element
JP2002105333A
Polyamide resin composition for insert mold
JP2003321606A
Polyamide resin composition
JP2014141630A